MICRO-FINANCE AND PORTFOLIO DIVERSIFICATION - Ahmad, Habib; Ali Shah, Syed Zulfiqar (Malaysian Journal of Business and Economics (MJBE), 2020)
The purpose of this paper is to investigate the impact on diversification benefits if microfinance stocks are included in a portfolio. Prices of different micro-finance stocks and data regarding stocks indices of respective countries are taken from Thomson One Banker database. To investigate whether diversification benefits may be enhanced or not by including microfinance stocks in one’s portfolio, the mean-variance spanning test is applied. Although the lesser or sometimes negative correlation between microfinance stocks and international portfolio is spotted no diversification benefits are identified by the inclusion of microfinance stocks in the portfolio. It may be because of the reason that most of the microfinance stocks are offering negative returns and therefore not attractive for the investors. The poor performance of micro-finance institutions maybe because of the two-fold objective of sustainability and social welfare or may be attributed to high operating cost bear by microfinance institutions. It means that microfinance may not offer good diversification opportunities. This is the first study of its kind that investigates to investigate the role of microfinance stocks in international diversification.